A-23 Mental Health Outcomes of Elite Athletes Following Sport Related Concussion. (18th June 2020) - Hoyle, C; Mrazik, M; Naidu, D
Abstract: Objective: Investigation of anxiety and depression symptoms at baseline and following sport related concussion in a population of professional and collegiate football players. Method: A quasi-experimental prospective longitudinal design was implemented. Participants included 198 Canadian Football League and University of Alberta varsity football players at baseline. Additionally, this study tracked 13 concussed athletes, 12 orthopaedic control athletes, and 15 healthy control athletes over approximately a 2 month period. Statistical analysis included an ANOVA and repeated measures ANOVA to identify differences in mental health at baseline as well as after injury at 3 time points (24-48 hours post injury, asymptomatic, and 1 month post return to play). Results: At baseline, players who had a history of 1 or more concussions reported a greater number of anxiety and depression symptoms in comparison to players who did not have a history of concussion (F(2, 197) = 66.75, (p =.000)). At the group level, there were no differences in anxiety and depression symptoms between players who sustained a concussion, orthoepic injury, or no injury across the four time points measured (depression (F(3, 58) = 1.05, (p =.404); anxiety (F(3, 58) = 1.65, (p =.151)). However, individuals who sustained a concussion displayed significant changes in symptoms of anxiety (F(3, 12) = 9.004, (p =.000)) and depression (F(3, 12) = 11.396, (p =.000)) over time. Specifically, concussed players reported an increase in anxiety related symptoms between baseline report and 24-48 hours post injury (p = .042), a decrease between 24-48 hours and 1 month post return to play (p = .002) and a decrease between asymptomatic and 1 month post return to play (p = .036) time points. Additionally, players who sustained a concussion reported a significant increase in depressive symptoms between 24-48 hours post injury and 1 month post return to play (p = .029) and a decrease between asymptomatic and 1 month post return to play (p = .014) time points. This change over time was not found in the orthopaedic injury (depression (F(3, 11) = 2.467, (p =.14); anxiety (F(3, 11) = 2.242, (p =.15)) or healthy control groups (depression; (F(3, 14) = 2.177, (p =.17); anxiety; F(3, 14) = 1.435, (p =.30)). Conclusions: Results from this study suggest that a history of concussion impacts baseline self-report of anxiety and depression symptoms. Furthermore, players who sustained a concussion experienced subtle increases in anxiety and depressive symptoms in the short term and not in the long term. Players with who sustained an orthopaedic injury and healthy players did not show these changes in anxiety and depression symptom report. It appears that in this small sample concussion produced unique outcomes related to mental health functioning in the short term.